2007
DOI: 10.1159/000103240
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Organizing Pneumonia: A Relapsing Disease

Abstract: Background: Although organizing pneumonia (OP) is a common pathological finding, studies including a substantial number of patients with idiopathic forms from a unique center and a long follow-up are rare. Objectives: To determine patients with cryptogenic forms of organizing pneumonia (COP), in order to characterize their clinical course, to identify predictive factors for relapse and to assess their effect on outcome. Methods: For a 19-year period, all histopathological reports from a community teaching hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 57 publications
(55 reference statements)
2
25
0
1
Order By: Relevance
“…However, there have been very few studies on the precipitating factors [42,43,44,45], and to the best of our knowledge, the hypothesis of a possible link with GERD has never been raised. Relapses in our study were defined as previously in the literature [42,43,45]. In a study of 18 cases of OP, Watanabe et al [42 ]found that the PaO 2 of relapsing patients (55 mm Hg) was significantly lower than that of patients with no relapse (78 mm Hg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been very few studies on the precipitating factors [42,43,44,45], and to the best of our knowledge, the hypothesis of a possible link with GERD has never been raised. Relapses in our study were defined as previously in the literature [42,43,45]. In a study of 18 cases of OP, Watanabe et al [42 ]found that the PaO 2 of relapsing patients (55 mm Hg) was significantly lower than that of patients with no relapse (78 mm Hg).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the patients in the 2 groups who had undergone pathological examination did not show significant differences with regard to collagen fibrosis. Lastly, Barroso et al [45 ]carried out a 19-year retrospective study of 33 cases of COP. They found that relapse was more common in cases with low levels of liver enzymes and with multifocal opacities, and that there was a tendency to relapse in cases with shorter corticosteroid treatment and rapid radiological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the prognosis of COP is good as most forms of COP will respond very well to steroid regardless of the in ltrative pattern on the imaging, if given promptly. Nevertheless, many patients end up being on a long-term steroid therapy due to a high rate of relapse [14] and up to 73% of the patients with COP would have residual disease seen on follow-up CT. In such cases, the lesions generally resemble a brotic nonspeci c interstitial pneumonia pattern that does not resolve even with complete clinical recovery [15].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and complete recovery is the expected response to corticosteroids in OP [10]. A dose ≥40 mg of prednisone was given, on average, for 7.5 weeks.…”
Section: Discussionmentioning
confidence: 99%